Syngas Production via Methane Dry Reforming over Ceria-Magnesia Mixed Oxide-Supported Nickel Catalysts - Al-Swai, B.M. (2019)
Dry reforming of methane (DRM) is becoming an appealing research topic because of the urgent need to minimize global warming and the demand for alternative energy resources. However, DRM commercialization and industrial scale application are limited by the deactivation of the applied catalysts. In this work, Ni-based catalysts supported on CeO2-MgO mixed oxides (0-20 CeO2 molar content) were prepared and employed in DRM. The support was synthesized via a coprecipitation method followed by impregnation of Ni metal. The catalysts prepared were characterized by X-ray diffraction, Brunauer-Emmett-Teller (BET) analysis, temperature-programmed reduction, X-ray photoelectron spectroscopy, and field emission scanning electron microscopy (FESEM) techniques. The catalytic performance of the catalysts was evaluated in a fixed-bed continuous reactor with an equimolar (CH4/CO2) ratio at 1073 K. The addition of CeO2, as a promoter to the support, altered the interaction between Ni and MgO and modulated the properties of the catalysts toward an excellent activity performance and multiwalled carbon nanotubes (MWCNTs) production. CeO2 significantly enhanced the BET surface area, promoted Ni dispersion, and improved the reducibility of the catalyst. Among the obtained catalysts, Ni/15CeO2-MgO achieved the maximum conversion of both CO2 (95.2) and CH4 (93.7) without significant deactivation during the reaction. The superior catalytic performance of the aforementioned catalyst is due to the presence of a high quantity of active Ni sites and the high Ce3+/Ce4+ ratio that promoted the formation of oxygen vacancies. With the aid of temperature-programmed oxidation, FESEM, transmission electron microscopy, and Raman spectroscopy analysis, it was found that the amorphous carbon encapsulated the active sites of the catalysts, in the absence of Ce, which suppressed the syngas production significantly. The introduction of Ce not only decreased the deposited carbon but also changed the type of the later to MWCNTs, which had positive effects on the activity of the catalyst. Â© 2018 American Chemical Society.